Sleep Duration and its Associated Factors among Residents of Hulu Langat, Selangor - Zahir Izuan Azhar; Mohd Rohaizat Hassan; Mohammad Saffree Jeffree (2016)
Background and Aims: Shorter and longer duration of sleep are known to be risk factors for diseases such as diabetes mellitus, hypertension and obesity. Most studies were done in the developed countries and there are limited population based data from Malaysia regarding this topic. The objective of this study is to determine the prevalence of short sleeping duration among residents in the Hulu Langat district and determine its associated factors. Methods: This was a cross-sectional study done in the year 2000. 7731 respondents in the Hulu Langat district were surveyed using a self-administered questionnaire. Short sleep duration was defined as having sleeping duration of less than 6 hours per day and long sleep duration as having sleeping duration of 6 hours or more per day. Results: The prevalence of short sleep duration was 6.2%. The mean age of participants was 43.2 years (±14.31) and 64.1% were females. Multiple logistic regression revealed significant association between short sleeping duration and younger age group (< 40 years old) (aOR=1.41, 95% CI: 1.15-1.73) and between short sleeping duration and smoking (aOR= 2.26, 95% CI: 1.57-3.26). Association between sleeping duration and gender, ethnicity, marital status, hypertension, diabetes and body mass index (BMI) were found to be not significant after multivariate analysis was done. Conclusion: This study shows that shorter sleeping duration is significantly associated with younger age group (<40 years old) and smoking. Health promotion strategies should aim to educate the public regarding getting adequate sleep and stop smoking.